Neonatal Seizures Revisited - Konrad Kaminiów; Sylwia Kozak; Justyna Paprocka (MDPI AG, 2021)
Seizures are the most common neurological disorder in newborns and are most prevalent in the neonatal period. They are mostly caused by severe disorders of the central nervous system (CNS). However, they can also be a sign of the immaturity of the infant's brain, which is characterized by the presence of specific factors that increase excitation and reduce inhibition. The most common disorders which result in acute brain damage and can manifest as seizures in neonates include hypoxic-ischemic encephalopathy (HIE), ischemic stroke, intracranial hemorrhage, infections of the CNS as well as electrolyte and biochemical disturbances. The therapeutic management of neonates and the prognosis are different depending on the etiology of the disorders that cause seizures which can lead to death or disability. Therefore, establishing a prompt diagnosis and implementing appropriate treatment are significant, as they can limit adverse long-term effects and improve outcomes. In this review paper, we present the latest reports on the etiology, pathomechanism, clinical symptoms and guidelines for the management of neonates with acute symptomatic seizures.